Three-Dimensional Characterization of Co/Pd Multilayer Thin Films Using Resonant Soft X-Ray Scattering - Escrig-Murua, J; Oyarzun-Medina, S; Michea-Mora, S; Casagrande-Denardin, J (American Physical Society, 2017)
In this work, we take a step toward nanometer resolution magnetic tomography, demonstrating the use of resonant magnetic x-ray scattering for three-dimensional (3D) characterization of Co/Pd multilayers. Trading coherence for x-ray flux, we measured magnetic scattering out to full period resolutions of 20 nm for incidence angles up to 75 from normal incidence, which was sufficient for a semiquantitative analysis of the 3D magnetic domain structure of such films. For the analysis of such patterns, we developed a scattering model based upon multiple plane propagation of the beam through the sample, taking into account the effects of multiple scattering not accounted for with Born or Rytov approximation based models. Our results demonstrate that 3D statistical characterization of nanoscale magnetic features is currently possible, and it is expected that the advent of high brilliance sources such as MAX IV in Sweden and SIRIUS in Brazil will provide the coherent flux necessary to permit the generalization of this work to nanometer resolution magnetic tomography. © 2017 American Physical Society.